Perbandingan Ekspresi PD-L1 dan TILS pada Karsinoma Payudara Triple Negative dan HER2 Enriched - Muhammad Asprianto; Krisna Murti; Citra Dewi; Erial Bahar (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2021)
BackgroundTriple negative and positive HER 2 subtype breast carcinoma are aggressive subtype that have worst prognosis among othersubtype. High level of tumor infiltrating lymphocytes (TILs) is associated with longer disease free survival and overall survival.Breast cancer is also influenced by the presence of ligation between PD-1 and PD-L1, expressed by activated CD8+ T cells andtumor cells, consecutively. To analysed the comparison of PD-L1 expression levels in triple negative breast cancer and HER2enriched subtype.MethodsA cross sectional study was conducted with 35 samples, which were immunostained with an anti-PD-L1 antibody. TILs weremeasured on HE slides, and together with PD-L1 expression were calculated using image J. Clinicopathological data were obtainedfrom medical record. All data were analysed by SPSS V25.0ResultsA significant difference was observed between PD-L1 expression in HER2 enriched and triple negative samples, where the HER2enriched subtype had a possibility to express PD-L1 3.3 times higher than those of triple negative (p = 0.021; OR = 3.3). There wereno significant differences in clinopathological characteristics or TILs density in both subtypes. Likewise, no significant differenceswas found among PD-L1 expression, and intratumoral and stromal TILs expression.ConclusionMajority patient of both subtypes are mostly older than 40 years old, with positive LVI and higher histological grading. The HER2expression showed a higher level of PD-L1 than triple negative. There was no significant difference of TILs expression betweenthese two subtypes of breast cancer.